Inhibitory effect of 2',3'-didehydro-2',3'-dideoxynucleosides on infectivity, cytopathic effects, and replication of human immunodeficiency virus - Yosuke Hamamoto; Hiroshi Nakashima; T Matsui; Akira Matsuda; Takuya Ueda; Naoki Yamamoto (1987)
It is generally accepted that human immunodeficiency virus (HIV) is the etiologic agent of the acquired immunodeficiency syndrome and related diseases. In this report, we demonstrate the antiviral effect of nucleoside analogs 2',3'-didehydro-2',3'-dideoxythymidine (DHT) and 2',3'-didehydro-2',3'-dideoxycytidine (DHC) by using human T-cell lymphotropic virus type I-carrying MT-4 cells, which are extremely susceptible to HIV infection. These agents efficiently inhibited the cytopathic effects and expression of HIV-specific antigens in MT-4 cells after infection of the virus. Both DHT and DHC also strongly blocked viral replication as determined by our quantitative bioassay system using a plaque-forming assay. These antiviral effects were obtained at concentrations at which the drugs produced little or no toxicity and were comparable to those with 3'-azido-3'-deoxythymidine and 2',3'-dideoxynucleosides. These findings warrant further investigation of the use of DHT and DHC for the treatment of the acquired immunodeficiency syndrome and related diseases.